Pengembangan Instrumen Keterampilan Berpikir Kritis pada Pembelajaran Matematika SMA - Harjo, Budi; Putra, Sudarmadi; Jaladri, Kafin; Subando, Joko (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to develop an instrument for assessing critical thinking skills that meets the criteria for validity, reliability, and good item quality.Method – Preliminary research identified challenges faced by mathematics teachers in designing valid and reliable assessment instruments for students' critical thinking skills. To address this, the study employed a literature review, expert validation, and both limited and expanded trials. Content validity was assessed using Aiken’s validity index, while construct validity and reliability were analyzed using Confirmatory Factor Analysis (CFA). Findings – The first-stage trial focused on assessing content validity through Aiken’s validity index. The results indicated that both the construction material and linguistic/readability aspects achieved validity values above 0.5, confirming the instrument’s suitability for high school mathematics learning. The subsequent expanded trial evaluated construct validity and reliability using CFA. The analysis demonstrated that all indicator factor loadings exceeded 0.5, confirming their validity, while construct reliability values exceeded 0.7, indicating reliability. Additionally, the model fit indices showed RMSEA < 0.08, p-value > 0.05, Chi-Square/df < 2, AGFI > 0.9, and GFI > 0.9, confirming that the developed model aligned well with the empirical data. Research Implications – The developed instrument effectively measures critical thinking skills in mathematics learning, meeting the criteria for a robust assessment tool with strong validity, reliability, and model fit. It is recommended for broader implementation in educational settings.